Global pro bono : causes, context, and contestation / Scott L. Cummings, Fabio De Sa E Silva, Louise G. Trubek. - Cummings, Scott L., 1969-; Silva, Fabio De Sa E, 1980-; Trubek, Louise G (Cambridge studies in law and society., 2022)
The principle and practice of pro bono, or volunteer legal services for the poor and other marginalized groups, is an increasingly important feature of justice systems around the world. Pro bono initiatives now exist in more than eighty countries - including Colombia, Portugal, Nigeria, and Singapore - and the list keeps growing. Covering the spread of pro bono across five continents, this book provides a unique data set permitting the first-ever comparative analysis of pro bono's growing role in the access to justice movement. The contributors are leading experts from around the world, whose chapters examine both the internal roots of and global influences on pro bono in transnational context. Global Pro Bono explores the dramatically expanding geographical and political reach of pro bono: documenting its essential contribution to bringing more justice to those on the margins, while underscoring its complex and contested meaning in different parts of the world.